Exploring the Profound Impact of Artificial Intelligence Applications (Quillbot, Grammarly and ChatGPT) on English Academic Writing: A Systematic Review - Bareq Raad Raheem; Farheen Anjum; Zanyar Nathir Ghafar (MultiTech Publisher, 2023)
The term